2021
DOI: 10.3350/cmh.2020.0125
|View full text |Cite
|
Sign up to set email alerts
|

<i>Lactobacillus</i> attenuates progression of nonalcoholic fatty liver disease by lowering cholesterol and steatosis

Abstract: Background/Aims: Nonalcoholic fatty liver disease (NAFLD) is closely related to gut-microbiome. There is a paucity of research on which strains of gut microbiota affect the progression of NAFLD. This study explored the NAFLD-associated microbiome in humans and the role of <i>Lactobacillus</i> in the progression of NAFLD in mice.Methods: The gut microbiome was analyzed via next-generation sequencing in healthy people (n=37) and NAFLD patients with elevated liver enzymes (n=57). Six-week-old male C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 46 publications
(67 reference statements)
3
36
0
1
Order By: Relevance
“…In general, the majority of these studies have addressed the effects of specific probiotic strains in animals challenged by diets leading to NAFLD. In this line, the administration of several probiotic strains (mainly Lactobacillus and Bifidobacterium ) has been shown to be effective in reducing liver lipid accumulation under dietary conditions providing 40 to 65% of energy as fat [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Moreover, this effect is also maintained when excessive hepatic lipid accumulation is mediated by dietary conditions providing high sugar intakes (10 to 30% of energy as fructose).…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the majority of these studies have addressed the effects of specific probiotic strains in animals challenged by diets leading to NAFLD. In this line, the administration of several probiotic strains (mainly Lactobacillus and Bifidobacterium ) has been shown to be effective in reducing liver lipid accumulation under dietary conditions providing 40 to 65% of energy as fat [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Moreover, this effect is also maintained when excessive hepatic lipid accumulation is mediated by dietary conditions providing high sugar intakes (10 to 30% of energy as fructose).…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 99%
“…There are also a number of studies that have addressed the effects induced by probiotic administration on gut microbiota composition, microbial metabolite production and intestinal barrier integrity, all processes involved in NAFLD pathogenesis. Thus, the majority of the studies have reported that single-strain probiotic administration prevented diet-induced gut microbiota dysbiosis, mainly by increasing bacterial diversity and Bacteroidetes relative abundance and/or decreasing the Firmicutes / Bacteroidetes ratio [ 16 , 18 , 20 , 24 , 25 , 29 , 31 , 37 ]. In addition, the enhanced gene and protein expression of intestinal tight-junction markers, such as Occludin-1, Zonula Occludens-1 or Claudin, suggests that single-strain probiotic administration is an effective approach preventing high-fat and/or high-sugar diets induced gut barrier function impairment [ 17 , 20 , 32 , 36 , 37 ].…”
Section: Effects Of Probiotic Administration (Single Strain and Mixtu...mentioning
confidence: 99%
“…We observed a species-specific increase of L. reuteri with a concurrent decrease in L. murinus suggesting shifts in Lactobacillus composition at the species and/or strain levels. Further, decreased abundance of L. murinus has been reported in human NAFLD [53]. Other taxa enriched following treatment included Turicibacter sanguinis, an anaerobic grampositive bacillus commonly found in animals, including humans [54].…”
Section: Discussionmentioning
confidence: 95%
“…This supported that Lactobacillus could modulate the microbiota; therefore, microbiota modulation by probiotics is being studied as one of the mechanisms to alleviate various diseases. Lactobacillus attenuated the progression of obesity-induced non-alcoholic fatty liver disease by regulating the microbiome [72]. In addition, the vaginal microbiota of nonpregnant sexually active women with diagnoses of bacterial vaginosis receiving L. rhamnosus BMX 54 was different from that of the untreated group.…”
Section: Mode Of Action As a Probioticmentioning
confidence: 95%